Identificación de la violencia epistémica como factor de la pérdida del conocimiento cultural de la comunidad Muisca en la Biblioteca Comunitaria Policarpa Salavarrieta del territorio Usmeka. (2021)
This research monograph seeks to identify epistemic violence as one of the main factors of cultural ignorance of the Muisca community, in the context of the Policarpa Salavarrieta Community Library. This library, located in the town of Usme, provides school strengthening and workshops for the entire community of the Santa Marta neighbourhood in the south of Bogota, DC.